The Urgency of Halal Assurance System for Product Reliability - Moch. Khoirul Anwar (International Journal of Islamic Business and Economics (IJIBEC), 2018)
Indonesia is a country with world most Moslem population. Thus, among other countries participated in Islamic Konference Organization, Indonesia is the biggest on product consumption market. This huge number of Moslem is crucial to be considered in business, particularly to the reliability of food product in Indonesia. This far, halal products is attributed with a certificate of halalness established by MUI (i.e, Indonesia Ulama Committee). However, the monitoring of halal products by companies with halal certificate may not be sustainably conducted by MUI, thus it needs a company system assuring that their products are halal. This study used a qualitative approach and was a field research. As a practival resource, this study was conducted in LPPOM MUI (i..e, Department of Assessment on Foods, Drugs, and Cosmetics by Indonesia Ulama Committee) East Java and another place related to this department. The data of this study was collected by participative observation or engaged observation and interview. Additionally, documentation in particular to the existing system of halalness by LPPOM MUI East Java was also applied. As the result, first, in order to assure the halalness of food products from halal−certified companies, it needed a Halal Assurance System. Second, this Halal Assurance System was made and applied by halal−certified companies to keep the sustainability of halalness on their products. Third, Halal Assurance System was an effort for customer satisfaction.